Perempuan Dalam Teks Satsra Arab:Pespektif Sosiolinguistik - Rusydi, Muhammad (PSW, 2014)
Abstract: Language and culture can be described as two sides of a coin that are fused to one another. Social phenomenon of arab society that still tends to treat woman as second-class society after the men who occupy the position of first grade has been recorded in variousÂ Arabic literary texts in their position as a product of science that should expands the missionÂ of social justice Â in under-standing social phenomena, serve as a means of justify-cation for structured social hegemony conducted bye men over woman in the frame of gender inquality. Socio-linguistic perspective, at least, can give an objective picture of how the actual social background surrounding the writing and the interpretating of Arabic literary text so that the text can be liberated from the spectrum between objectivity and subjectivity.